(3fgGjI GdWdH aj TQM GdecJSH aj RQGYI GdPgHs - (3GdLdOcqj, YR GdOjf, Ydj Hf eMeO Hf CjOeQ, J HYO (B742 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj JYGdi Yf GdYdd hGdeYdhdGJKe hVYfG eUMafG GdeSei HGdTeS GdefjQ aj JMbjb GdCcSjQ Ke hVYfG cJGHfG gPG GdeSei HfgGjI GdWdH aj TQM GdecJSH dCfG GWdYfG Ydi eJf gPG GdcJGH GdPj gh GdecJSH aj RQGYI GdPgH hLOfGg cdg Ydi GdUhGHs
(3BNQgG (B:s
(3hGdGYJeGO Ydi Gddg gh GdCUd GdeJjf hGdJhcd Ydi Gddg gh GdUQGW GdeSJbje hGdGgJOGA Hg gh GdfhQ GdeHjf hGdJeSc HLfGHg JYGdi gh GdebUhO agh GdZGjI GdbUhi hGdfgGjI GdYXeis
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 1 / 415s
(3cTa GdXfhf(B: 2 / 1811s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs